Wings of fire : an autobiography - Abdul Kalam, A. P. J. (Avul Pakir Jainulabdeen), 1931-; Tiwari, Arun. (Hyderabad, A.P., India : Universities Press : Distributed by Orient Longman, 1999)
Autobiography of an Indian scientist.
Donated By Akbar Ali Khan
Keywords: Abdul Kalam, A. P. J. -- 1931-; Scientists -- India -- Biography